Experimental Investigations of Injection and Combustion Parameters of a Homogeneous Charge Compression Ignition (HCCI) Engine with a Multi-Injection Common Rail System - Niklawy, Waleed; Shahin, Moatasem; Amin, Mohamed I.; Elmaihy, Ali (Communications - Scientific Letters of the University of Zilina, 2022)
This work experimentally investigates the most imperative parameters that control the injection and combustion processes in a multi-injection HCCI Diesel engine namely; fuel-line pressure, timing of multi-injection events and the resulting in-cylinder pressure. These parameters in addition to the heat release rates are evaluated at different engine loads and speeds over up to 42 successive cycles. The main inter-relations of these parameters are also discussed.
Keywords: HCCI; fuel line pressure; AHRR; injector activation signals; multi-injections CR system